The Effect of Pliometric Training on Front Kick Speed In Pencak Silat - Indrayogi, Indrayogi; Fauzi, Riza Sukma; Yudha, Brio Alfatihah Rama (Media Ilmu Keolahragaan Indonesia, 2024)
From the results of the author's observations, in the pencak silat extracurricular during training, that in terms of the use of front kicks there are still children who do not have kicking speed when performing straight kicking techniques due to lack of attention to speed training exercises on the muscle part, this can be seen when kicking the athlete does not reach maximum speed. The purpose of this study was to determine whether there is an effect of pliometric training on increasing the speed of the front kick of pencak silat at SMAN 1 Maja. The method used is experimental method with One Group Pretest-postest Design research design. The number of samples was 20 people, with total sampling technique. While the instrument uses a front kick martial arts test. From the results of hypothesis testing, the value of 0.015 is smaller than 0.5, it can be said that the hypothesis is accepted, this means that there is an effect of pliometric training on increasing the speed of front kicks.